ZnO-modified hybrid polymers as an antibacterial finish for textiles. Issue 1 (January 2014) - Farouk, Asmaa; Moussa, Shaaban; Ulbricht, Mathias; Schollmeyer, Eckhard; Textor, Torsten
The antibacterial activity of ZnO is reported by several authors. We present the preparation and application of inorganic–organic hybrid polymers modified/filled with ZnO nanoparticles of varying particle sizes. Inorganic–organic hybrid polymers employed here are based on 3-glycidyloxypropyltrimethoxysilane (GPTMS). ZnO is prepared by hydrolysis of zinc acetate in different solvents (methanol, ethanol or 2-propanol) using lithium hydroxide (LiOH ċ H2 O). The hybrid materials prepared are applied to cotton (100%) and cotton/polyester (65/35%) fabrics. The antibacterial performance of these sol-gel derived hybrid materials is exemplarily investigated against Gram-negative bacterium Escherichia coli and Gram–positive Micrococcus luteus . Effects of particle size and concentration for the antibacterial performance are examined. Literature discusses various (active) species and processes responsible for the antibacterial action of ZnO. Therefore, particular attention is paid to investigate active species available in the described systems as well as to observe possible interaction between the nanoparticles and bacteria; the first results are presented.